ANALISIS KETERAMPILAN LITERASI MEMBACA PERMULAAN BERBASIS WORDWALL PESERTA DIDIK KELAS I SD MUHAMMADIYAH KUTOARJO KABUPATEN PURWOREJO TAHUN PELAJARAN 2024/2025 - Yulianti, Triami Dina; Listyarini, Ikha; Budiman, Muhammad Arief (Fakultas Ilmu Pendidikan, Universitas Persatuan Guru Republik Indonesia Semarang, 2025)
This study aims to analyze the early reading literacy skills based on the use of Word Wall media for first-grade students at SD Muhammadiyah Kutoarjo, Purworejo Regency, in the 2024/2025 academic year. Early reading literacy is a fundamental skill that students must master in the learning process, including the ability to recognize symbols, read letters, identify letter sounds, read syllables, and read words. This research employed a descriptive qualitative method. Data were collected through observation, interviews, and documentation techniques. The results showed that students' early reading literacy skills were still low before the implementation of Word Wall media. After applying the Word Wall media, students found it easier to recognize symbols, letters, letter sounds, syllables, and words. Moreover, the use of Word Wall media increased students' interest and motivation in learning early reading skills. Thus, the implementation of Word Wall media proved to be effective in improving early reading literacy skills among first-grade students. It is expected that this study can be an alternative strategy for teachers to apply creative and engaging learning methods in teaching early reading at the elementary school level.